2004
DOI: 10.1097/01.qai.0000141251.16099.74
|View full text |Cite
|
Sign up to set email alerts
|

HIV Health Care Services For Mexican Migrants

Abstract: This article reviews the literature on HIV/AIDS health care services for Mexican migrants in the United States. Because so little research has been conducted on Mexican migrants per se, we include literature on Latinos/Hispanics in the United States, because some characteristics may be shared. Furthermore, we focus special attention on data from California because it is on the front line of issues regarding health care for Mexican migrants. The types of health care services needed to improve on the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
1
24
1
Order By: Relevance
“…5 Due to their undocumented status and hidden nature, the study population has traditionally remained off the radar screen of health departments, hospitals, and other sources of health indicators. Data on migrant workers presented in this paper come from the works of several researchers (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), fact sheets compiled by the National Center for Farmworker Health (15), and an investigative report published by the Palm Beach Post (16).…”
Section: Discussionmentioning
confidence: 99%
“…5 Due to their undocumented status and hidden nature, the study population has traditionally remained off the radar screen of health departments, hospitals, and other sources of health indicators. Data on migrant workers presented in this paper come from the works of several researchers (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), fact sheets compiled by the National Center for Farmworker Health (15), and an investigative report published by the Palm Beach Post (16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews of published data regarding HIV in migrant workers have focused on the Southeastern United States (Painter, 2008). These reviews have analyzed the epidemiology of HIV in migrants (Sanchez et al, 2004), reviewed U.S. health care services for Mexican migrants (Solorio, Currier, & Cunningham, 2004), reviewed and critiqued HIV prevention strategies for migrants (Organista, Carrillo, & Ayala, 2004), and given an overview of migration and AIDS in Mexico (Magis-Rodriguez et al, 2004). Only one review offered an overall analysis of migrants and HIV in the United States; however, this review is now outdated (Organista & Organista, 1997).…”
Section: Mexican Migrant Workers Residing In the Unitedmentioning
confidence: 98%
“…Although services do exist for migrant workers (Solorio et al, 2004), the federal Migrant Health Program has been critiqued for having inadequate resources to meet the needs of this large population (Villarejo, 2003). Previously published data show that migrant workers have little interaction with the traditional U.S. health care system, seeking costly emergency care only when absolutely essential.…”
Section: Environmental Resourcesmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding is consistent with national findings that foreign birth is a strong predictor of late HIV testing in the U.S. [21][22][23][24] Research has shown that undocumented status, lack of health insurance, perceived lack of risk, and stigma contribute to delayed HIV testing among foreign-born people. 22,25,26 Foreign-born people often have limited access to care. 27 Low-cost HIV testing outside of traditional health-care settings, education on HIV risks, and promotion of early testing and care may increase early HIV diagnosis among foreign-born patients.…”
Section: Discussionmentioning
confidence: 99%